ETHNOBOTANY OF MEDICINAL PLANTS IN VUNATUI CLAN OF THE TOLAI SOCIETY IN EAST NEW BRITAIN PROVINCE, PAPUA NEW GUINEA - Felicitas Bureng; J Jumari; Jafron Wasiq Hidayat (Jurnal Akademika Biologi, 2016)
Traditional knowledge of medicinal plant use in many regions of Papua New Guinea and the East New Britain Province is poorly described and rapidly disappearing due to some factors like religion and outside influence that may have contributed to the fading away of indigenous knowledge within each ethnic group. The main aim of this  research was to identify some of the plants used as medicinal plants in the Vunatui clan of the Tolai society in East New Britain, PNG and determine the type of disease or conditions being treated by these plants and how the plants are being prepared. The main data of this researched was compiled through consultation and interview with three of the traditional doctors “tena dawai” within the clan who helped to provide the information on plants used as medicine. Although most of the traditional or indigenous knowledge in East New Britain are based on secrecy and must be paid for in some circumstances if one wants to learn or know about it, the medicinal doctors were willing to provide information after they were made aware of the purpose and benefit of this research. There were about 50 species of plants gathered in this research and there is variation shown among the plants. The plants range from herbaceous to vines, shrubs and trees and were found on the coastal areas to mid- mountains of the area of study. Different methods of preparartion were used but the most common method used was infusion. From the methods of applications that were used, oral administration was the most common.Key words: Traditional medicinal plants, Vunatui Clan, tena dawai,